(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2019)
A Mobile Ad-Hoc Network (MANET) is a collection of mobile nodes (such as laptops, PDAs) forming an arbitrary networks without the support of any fixed infrastructure such as base station or access point. In MANET, each node functions as a router and forwards packets to other peer nodes. There is no fixed topology due to the node mobility, which results in interference, multipath propagation and path loss. Mobile nodes have constraints on battery power, computation capacity, bandwidth, and wireless channel leading to number of challenges while designing routing procedures. Determining viable routing paths and delivering messages in a decentralized environment where network topology fluctuates has always attracted the attention of researchers to design new and new mechanism to solve these problems. While the shortest path (based on a given cost function) from a source to a destination in a static network is usually the optimal route, this idea is not easily extended to MANET In this paper, the work proposed a stability aware of Optimized Overhead internet gateway discovery in Mobile Ad-hoc Network that is capable of predicting the stability (i.e., expiration time) of multiple routes. AODV then selects the route that minimizes hop count while staying available for the expected duration of packet transmission. The proposed protocol increases the successful packet transmissions with comparable route establishment and maintenance overheads. A new approach in Ad-Hoc on Demand Routing Protocol (AODV) is based on the prediction of future sleep times of mobile nodes (i.e., the times when mobile nodes’ Selective Forward techniques will turn Mobile Router Advertisement (MRA) their network cards). The goal of this approach is to introduce Optimized-Overhead awareness in routing decisions and thereby to increase the number of successful packet transmissions.